Back Cover: Atomic cerium modulated palladium nanoclusters exsolved ferrite catalysts for lean methane conversion (EXP2 6/2022). Issue 6 (18th December 2022) - Yang, Yanling; Wang, Si; Tu, Xin; Hu, Zhiwei; Zhu, Yinlong; Guo, Hongquan; Li, Zhishan; Zhang, Li; Peng, Meilan; Jia, Lichao; Yang, Meiting; Yang, Guangming; et al.
Abstract : The efficient conversion of CH4 is of great environmental and industrial significance. N2 as an optimal activation agent to develop a Pd nanocluster exsolved Ce‐incorporated perovskite ferrite catalyst toward lean methane oxidation. The isolated Ce at the A‐site of perovskite facilitates the thermodynamic and kinetics of the Pd exsolution process, lowering the Pd nanocluster formation temperature and promoting its quantity.